Novel method for protein microencapsulation in polyelectrolyte microparticles. - Sharon Harvinder Kaur Dhillon. (2011)
Tremendous advancements in proteomics have aroused great interest in the development of protein therapeutics for human ailments, thereby increasing the demand for innovative, safe and efficient protein delivery methods. Polyelectrolyte microparticles (PEMP) represent a novel type of highly customizable carrier system for the delivery of bioactive therapeutics. PEMP are fabricated by the layer-by-layer (LbL) adsorption of oppositely charged polyelectrolytes onto a colloidal template and can be customized by varying properties such as multilayer composition and colloidal template used. This study aims to investigate a novel microencapsulation technique via the incorporation of proteins as a layer constituent within polyelectrolyte multilayers, to ultimately fabricate PEMP for protein delivery purposes. Biodegradable and biocompatible PEMP were formed by the LbL adsorption of PRM/DXS polyelectrolytes onto a CaCO3 colloidal core. Model proteins lysozyme and BSA were separately adsorbed within PRM/DXS multilayer shells and the formation and stability of protein-loaded multilayers was confirmed using confocal microscopy, flow cytometry and zeta potential measurements.